Korean for short-term learners 2 - Kang, Seung-hae (Fast & fun Korean for short-term learners Series, 2009)
Provides a solid framework from which even those who have no previous experience with the language can learn basic Korean with minimal effort. • Essential vocabulary, grammar patterns, and dialogues chosen based on their real-life usefulness. • Comprehensive approach incorporating speaking, listening, reading, and writing skills in a variety of task exercises. • Linked study and review process of Warming up - Pattern Practice - Key Grammatical Patterns - Conversation Practice